Personality and Learning Creativity of The Students With English Learning Achievement - Nabila, Ayu (JoLLIET, 2015)
The purpose of this research is to get: (1) the correlation between students âPersonality with students âEnglish Achievement; (2) the correlation between students Creativity with students âEnglish Achievement; (3) the correlation between students Personality and students âCreativity simultaneously with students âEnglish Achievement. This research is a correlation research. It involves three variables that consist of two independent variables and one dependent variable. The two independent variables are the students Personality and students Creativity; while the one dependent variable is the English Achievement. This research population isÂ class XI students of Automotive and Engineering Department of SMK Pancasila Surakarta. The research population consists of 196 students with a sample size of 132 students. Sampling technique was proportional random sampling. The instruments were questionnaires and documentation. The questionnaires were used to measure the Personality and Creativity Variables. The documentation was used to obtain the scores of English Achievement. The data were analyzed by using partial correlation and multiple regression technique. The results of the research showed that (1) there was a positive and significant correlation between students Personality with the studentsâ English Achievement; (2) there was a positive and significant correlation between students Creativity with studentsâ English Achievement; (3) there were positive and significant correlation between students Personality and students Creativity simultaneously with studentsâ English Achievement.